Peroxisome Proliferator-Activated Receptor Modulation during Metabolic Diseases and Cancers: Master and Minions - Salvatore Giovanni Vitale; Antonio Simone Laganà; Angela Nigro; Valentina Lucia La Rosa; Paola Rossetti; Agnese Maria Chiara Rapisarda; Sandro La Vignera; Rosita Angela Condorelli; Francesco Corrado; Massimo Buscema; Rosario D’Anna (PPAR Research)
The prevalence of obesity and metabolic diseases (such as type 2 diabetes mellitus, dyslipidaemia, and cardiovascular diseases) has increased in the last decade, in both industrialized and developing countries. This also coincided with our observation of a similar increase in the prevalence of cancers. The aetiology of these diseases is very complex and involves genetic, nutritional, and environmental factors. Much evidence indicates the central role undertaken by peroxisome proliferator-activated receptors (PPARs) in the development of these disorders. Due to the fact that their ligands could become crucial in future target-therapies, PPARs have therefore become the focal point of much research. Based on this evidence, this narrative review was written with the purpose of outlining the effects of PPARs, their actions, and their prospective uses in metabolic diseases and cancers.